The Accountability of Islamic Microfinance Institution: Evidence from Indonesia - Ersa Tri Wahyuni (The Winners, 2008)
The article aims to provide current condition’s information on the accountability of Baitul Maal wat Tamwil (BMT) in Indonesia. Lack of supervisory board and low demand for audited financial statements provide little incentive for BMT managers to make their financial statement audited by independent auditor. Statistical estimation technique about one sample proportion, give an estimation with 95% confidence level that only 7-20% of BMT is audited by independent auditor. Most of the reason for BMT not being audited are because they feel they do not need an audit and the price for audit is relatively expensive.